Per- and polyfluoroalkyl substances exert strong inhibition towards human carboxylesterases. (August 2020) - Liu, Yong-Zhe; Pan, Li-Hua; Bai, Yu; Yang, Kun; Dong, Pei-Pei; Fang, Zhong-Ze
Abstract: PFASs are highly persistent in both natural and living environment, and pose a significant risk for wildlife and human beings. The present study was carried out to determine the inhibitory behaviours of fourteen PFASs on metabolic activity of two major isoforms of carboxylesterases (CES). The probe substrates 2-(2-benzoyl-3-methoxyphenyl) benzothiazole (BMBT) for CES1 and fluorescein diacetate (FD) for CES2 were utilized to determine the inhibitory potentials of PFASs on CES in vitro . The results demonstrated that perfluorododecanoic acid (PFDoA), perfluorotetradecanoic acid (PFTA) and perfluorooctadecanoic acid (PFOcDA) strongly inhibited CES1 and CES2. The half inhibition concentration (IC50 ) value of PFDoA, PFTA and PFOcDA for CES1 inhibition was 10.6 μM, 13.4 μM and 12.6 μM, respectively. The IC50 for the inhibition of PFDoA, PFTA and PFOcDA towards CES2 were calculated to be 9.56 μM, 17.2 μM and 8.73 μM, respectively. PFDoA, PFTA and PFOcDA exhibited noncompetitive inhibition towards both CES1 and CES2. The inhibition kinetics parameters (Ki ) were 27.7 μM, 26.9 μM, 11.9 μM, 4.04 μM, 29.1 μM, 27.4 μM for PFDoA-CES1, PFTA-CES1, PFOcDA-CES1, PFDoA-CES2, PFTA-CES2, PFOcDA-CES2, respectively. In vitro-in vivo extrapolation ( IVIVE ) predicted that when the plasma concentrations of PFDoA, PFTA and PFOcDA were greater than 2.77 μM, 2.69 μM and 1.19 μM, respectively, it might interfere with the metabolic reaction catalyzed by CES1 in vivo ; when the plasma concentrations of PFDoA, PFTA and PFOcDA were greater than 0.40 μM, 2.91 μM, 2.74 μM, it might interfere with the metabolic reaction catalyzed by CES2 in vivo . Molecular docking was used to explore the interactions between PFASs and CES. In conclusion, PFASs were found to cause inhibitory effects on CES in vitro, and this finding would provide an important experimental basis for further in vivo testing of PFASs focused on CES inhibition endpoints. Graphical abstract: Image 1 Highlights: Longer-chain perfluoroalkyl substances strongly inhibited carboxylesterase. The higher binding affinity caused more severe inhibition. Inhibition kinetics was studied, and in vitro-in vivo extrapolation was performed.